(untitled) (Interdisciplinary Studies Journal, 2025)
This study aims to recount and reflect on the experiences gained during a supervised pedagogy internship process. It is important to note that this research is presented as a firsthand account by the main author. The internship took place over approximately two months at a public school in Parintins, Amazonas, Brazil, specifically with a class of 2nd graders in elementary school. The activities designed by the intern, as a graduating teacher, allowed her to grasp the dynamics of the classroom and the pedagogical practices in context, while systematic observations contributed to a critical analysis of teaching practices and helped identify challenges within the school routine. The teaching plan emphasized the cross-cutting theme of “environment”, adopting a pedagogical approach that values interdisciplinarity and contextualizes environmental content. The planned activities considered the school curriculum, the proposed cross-cutting theme, and the students’ real-life contexts aimed not only at theoretical learning but also at engaging students in practical and reflective ways. These practices fostered both cognitive and socio-emotional skills development, equipping students for meaningful learning and active participation in society.